(untitled) (Research, Society and Development, 2021)
This is an experience report about a work done in a Science Fair, about Environmental Education and sustainability, using the teenage pregnancy theme at Colégio Estadual Deputado Olívio Belich in Curitiba - Paraná. The objective was to raise the students’ awareness about the importance of knowing and respecting one’s own body, the seriousness of using contraceptive methods, the responsibilities, the environmental impact caused to the environment, the expenses, and the decomposition time of the products used by a child in the first years of life. Thus, we reflected: how can the theme contraceptive methods and pregnancy be related to Environmental Education? In the first moment, the psychological, physical, and hormonal changes that occur during puberty were explained, followed by the presentation of the most common contraceptive methods and a conversation about pregnancy in adolescence. After that, the students searched for information about which items are used by babies until they are three years old, the amount and volume of waste produced, the decomposition time, the care one should have with a baby, and the price of contraceptive methods to produce stands at the science fair. It was verified that the students had an effective participation in the activities about the theme of pregnancy in adolescence, sensitizing the school community in the science fair about the importance of taking care of one’s own body, the use of condoms to avoid contamination by diseases, the seriousness of contraceptive methods, and the impacts of an unplanned pregnancy on one’s own life.